Synthesis, spectroscopy, electrochemistry and in situ spectroelectrochemistry of partly halogenated coumarin phthalonitrile and corresponding metal-free, cobalt and zinc phthalocyanines - ÖZKAYA, ALİ RIZA (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
In this study, the preparation of novel 7-hydroxy-3-(2-chloro-4-fluorophenyl)coumarin (1), the ligand, 7-(3,4-dicyanophenoxy)-3-(2-chloro-4-fluorophenyl)coumarin (2), metal-free phthalocyanine 3 and metallophthalocyanine complexes 4 and 5 (MPcs, M = Co, Zn), beta-substituted with 7-oxo-3-(2-chloro-4fluorophenyl)coumarin functional group was achieved. By the reaction of 7-hydroxy-3-(2-chloro-4-fluorophenyl)coumarin (1) with 1,2-dicyano-4-nitrobenzen in dry DMF as the solvent in the presence of K2CO3 as the base, the 7-(3,4-dicyanophenoxy)-3-(2-chloro-4-fluorophenyl)coumarin (2) was synthesized. Compound 2 reacted with Co(CH3COO)2 center dot 4H(2)O in 2-N,N-dimethylaminoethanol to furnish a novel coumarin containing cobalt(II) Phthalocyanine 4. The cyclotetramerization of 2 with Zn(CH3COO)(2)center dot 2H(2)O in 2-N,N-dimethylaminoethanol gave the novel coumarin containing Zn(II)phthalocyanine 5; while tetramerization without any metal salts in 2-N,N-dimethylaminoethanol gave the metal-free phthalocyanine 3. The structures of obtained compounds were confirmed by elemental analysis. UV-Vis, IR, MALDI-TOF mass and H-1 NMR spectra. The cyclic and differential pulse voltammetry, and in situ spectroelectrochemistry of 7-oxo-3-(2-chloro-4-fuorophenyl)coumarin substituted phthalocyanines 3, 4 and 5 allowed us to identify metal- and phthalocyanine ring-based redox processes of the complexes. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Coumarin; Cobalt; Zinc; Phthalocyanines; Electrochemistry; Spectroelectrochemistry; SUBSTITUTED COBALT; COMPLEXES; DERIVATIVES; BEARING; ACID; BENZYLMERCAPTO; ANTITUMOR; ZN(II); SERIES